Comparação da densidade mineral óssea de atletas do sexo masculino praticantes de diferentes modalidades esportivas - Albuquerque, Rodrigo Barbosa de (2010)
The aim of this study was to assess and compare the bone mineral density (BMD): total and regional (legs, spine, pelvis and arms) of athletes from four sports: volleyball (VA), soccer (SA), swimming (SA) and cycling (CA) and a control group (CG). The sample was selected conveniently, was composed by 51 subjects: 10 SA (21,28 ± 4,43 years, 74,75 ± 6,63 kg and 1,78 ± 0,06 m), 11 VA (20,10 ± 1,34 years, 81,27 ± 8,89 kg and 1,86 ± 0,07 m), 10 SA (22,2 ± 3,92 years, 73,61 ± 16,55 kg; 1,76 ± 0,08 m), 10 CA (29,06 ± 1,45 years, 71,00 ± 11,31 kg, 1,71 ± 0,08 m) and 10 subjects who formed the CG (24,59 ± 2,75 years, 72,85 ± 10,52 kg, 1,73 ± 0,05 m). The BMD, total and regional levels were measured and compared using ANOVA and post hoc LSD beyond the ANCOVA to lessen the effects of intervening variables, with the level of p <0,05. Mean value for BMD total of SA was 1,31 ± 0,09, BMD of the legs of that group was 1,55 ± 0,09, BMD of the arms had mean score of 0,92 ± 0,10, BMD of the spine and BMD of the pelvis was 1,21 ± 0,13 and 1,47 ± 0,12, for VA, the results of BMD total, BMD leg, BMD of the arms, spine and pelvis were respectively 1,35 ± 0,08, 1,58 ± 0,11, 1,00 ± 0,07, 1,25 ± 0,14, 1,45 ± 0,21 for SA the average results for the BMD total BMD of the legs, BMD arms, BMD of the spine and pelvis, were respectively 1,21 ± 0,05, 1,32 ± 0,11, 0,93 ± 0,07, 1,12 ± 0,13 and 1,25 ± 0,11, for CA the BMD total, legs, arms, spine and pelvis were respectively 1,26 ± 0,15, 1,43 ± 0,22, 1,11 ± 0,38, 1,13 ± 0,11 and 1,27 ± 0,19 for control group, the average performance of the same BMD were respectively 1,29 ± 0,09, 1,47 ± 0,14, 1,00 ± 0,10, 1,17 ± 0,13 and 1,30 ± 0,17.The BMD of the legs of VA and SA was greater than that of SA, the VA also showed superiority of this BMD than the CA. This same BMD in SA was lower than the CG. Thus, it can be concluded that VA and SA can present, at least with respect to the BMD of the lower limbs, the greater osteogenic response and possible protection against bone loss in old age, while athletes in sports with less participation of gravitational force or impact, particularly swimmers may not experience significant stress to promote osteogenic responses.